Programa educativo aprendizaje invertido para desarrollar capacidades comunicativas en estudiantes ingresantes de Educación Primaria de la Facultad de Ciencias de la Educación y Humanidades en la Universidad Nacional de la Amazonía Peruana Iquitos 2023 - Vargas Tello, Diana Sofia (2025)
The study assessed the effect of an educational program based on flipped learning to enhance communicative skills in first-year Primary Education students at the Faculty of Education and Humanities, National University of the Peruvian Amazon, Iquitos, in 2023. The research employed an evaluative, longitudinal, univariate, field-based, and pre-experimental design. The population and sample consisted of 30 students. Data collection was carried out using a test validated by experts. The findings demonstrated a favorable and statistically significant effect of the program on communicative skills, evidenced by an increase in higher performance levels and a decrease in lower levels. These results underscore the effectiveness of flipped learning as an educational method to enhance students' communicative competencies, suggesting its application in other university educational contexts to optimize teaching-learning processes.